2015
DOI: 10.1186/s12906-015-0618-3
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness training for smokers via web-based video instruction with phone support: a prospective observational study

Abstract: BackgroundMany smokers are unable to access effective behavioral smoking cessation therapies due to location, financial limitations, schedule, transportation issues or other reasons. We report results from a prospective observational study in which a promising novel behavioral intervention, Mindfulness Training for Smokers was provided via web-based video instruction with telephone-based counseling support.MethodsData were collected on 26 low socioeconomic status smokers. Participants were asked to watch eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Several types of meditation have been studied as interventions to facilitate smoking cessation (Table ). Small studies have shown that mindfulness training, a form of meditation, increases abstinence rates when compared with more traditional intervention programs. In 1 study of volunteers wishing to reduce stress, half of whom were smokers, who were randomized to either a 2‐week program of integrative body‐mind technique—a form of mindfulness meditation—or relaxation training, a 60% reduction in smoking was observed among those instructed in integrative body‐mind technique, with no reduction in those instructed in relaxation training.…”
Section: Effects Of Meditation On Smoking and Tobacco Usementioning
confidence: 99%
“…Several types of meditation have been studied as interventions to facilitate smoking cessation (Table ). Small studies have shown that mindfulness training, a form of meditation, increases abstinence rates when compared with more traditional intervention programs. In 1 study of volunteers wishing to reduce stress, half of whom were smokers, who were randomized to either a 2‐week program of integrative body‐mind technique—a form of mindfulness meditation—or relaxation training, a 60% reduction in smoking was observed among those instructed in integrative body‐mind technique, with no reduction in those instructed in relaxation training.…”
Section: Effects Of Meditation On Smoking and Tobacco Usementioning
confidence: 99%
“…More recently, a mindfulness intervention called “Mindfulness Training for Smokers” reported significant differences in abstinence between treatment initiators and controls in a disadvantaged population (39 vs 21 %), but no difference in a more generalizable population (25 vs 18 %) [33]. There is very recent early evidence that expansion into app- and web-based delivery may be effective [3436]. The intervention findings are supported by a meta-analysis of 11 observational studies that showed significant inverse associations between dispositional mindfulness and smoking (aggregate r =−0.14; p <0.001) [37].…”
Section: Smokingmentioning
confidence: 99%
“…A recent study on a different intervention named “Mindfulness Training for Smokers” showed significant differences between treatment vs. control groups in a disadvantaged population, but no difference in a more generalizable population [62]. Finally, there have been a number of recent reports suggesting that app- and web-based delivery of mindfulness interventions have promise in smoking cessation [6365]. Studies are moving forward in identifying active components of the mindfulness interventions, and subgroups of people for whom the interventions may be most effective.…”
Section: Mindfulness-based Interventions For Cardiovascular Disease Rmentioning
confidence: 99%